Demethoxycurcumin-Metal Complexes: Fragmentation and Comparison with Curcumin-Metal Complexes, as Studied by ESI-MS/MS. (29th August 2013) - Ostrowski, Wojciech; Śniecikowska, Lidia; Hoffmann, Marcin; Frański, Rafał
Abstract : Two questions are asked: the first is if the lack/presence of methoxyl moiety at aromatic ring essentially affects the stability of curcuminoid-metal complexes, and the second is if it is possible that in the metal complexes one of the possible demethoxycurcumin structures predominates. To answer the first question, the ESI-MS/MS spectra were taken of ions containing demethoxycurcumin, curcumin, and metal cation (e.g., ion [dCurc + Curc-H + Pb] + ), and in order to answer the second question the ESI-MS/MS spectra were recorded of ions containing demethoxycurcumin and metal cation (e.g., ion [dCurc-H + Zn] + ). An interpretation of the mass spectra has indicated that (i) for some metals, curcumin-metal complexes are more stable than demethoxycurcumin-metal complexes and for some metals vice versa, and (ii) in demethoxycurcumin-metal complexes structure B1 [(1 E, 4 Z, 6 E )-5-hydroxy-7-(4-hydroxy-3-methoxyphenyl)-1-(4-hydroxyphenyl)hepta-1, 4, 6-trien-3-one] is more stable than structure B2 [(1 E, 4 Z, 6 E )-5-hydroxy-1-(4-hydroxy-3-methoxyphenyl)-7-(4-hydroxyphenyl)hepta-1, 4, 6-trien-3-one].